Thematic cups and the acceptance of high-protein oral supplements for children and adolescents with cancer - Beatriz Tereza Romano Bispo; Adriana Garófolo; Priscila Sala Kobal (O Mundo da Saúde, 2022)
Early nutritional intervention in children with cancer, associated with the use of high-protein oral nutrition supplements (OS), is of utmost importance. When it comes to children, it is important to highlight the relevance of the presentation of the utensils offered in the meals. The better acceptance of OS, when offered in a themed cup, can contribute to an improvement in the nutritional status and a better prognosis of the treatment. The objective of this study was to evaluate the acceptance of the fortified artisanal supplement mix, presented in two different ways: disposable cups versus themed cups, for children and adolescents undergoing cancer treatment. This is a prospective study carried out with children and adolescents undergoing cancer treatment. In the 1st stage of the study, the patients received the supplement in themed cups and in the 2nd stage they received the supplement in a disposable cup. Acceptance was assessed using the hedonic and numerical scales. 44 children and adolescents used the disposable cup and 36 the themed cup. The offer of different cups did not interfere with the acceptance of the supplement (p>0.3). However, the numerical scale presented a higher average score in the presentation of the themed cup (p<0.005), where 90% of children and adolescents who accepted ≥ 50% reported “liked” and “loved” (p<0.005), also obtaining a difference. As for the score for the variables: color, taste, texture, and odor (p<0.005). The data obtained in this study showed that the themed cup did not influence the increase in the consumption of the supplement but reinforced that the presentation of thematic utensils used for the meals of children and adolescents can be a beneficial strategy to reduce malnutrition in cancer patients.